Expectativas dos alunos concluintes do ensino médio público estadual com relação ao ingresso no ensino superior: conhecimento do ProUni e FIES - Silva, Ricardo Tadeu da (2009)
The present dissertation is the result of a research accomplished in 2008, aiming to analyze the reasons that lead students who finish high school at public state net in Northwest area of Sao Paulo to intend to enter public or private colleges. The aim of the research is to analyze the knowledge that students who attend evening classes at the public state net have about the federal government programs (ProUni and FIES), as expectation and expression of being admitted at private colleges. The data collection was made through a questionary, collection fundamental basis. Pierre Bourdieu s cultural, economical and social capital concepts were used on the analysis, as well as Maria Alice Foracchi s and Maria Helena Augusto s works, sources for understanding the expectations of students who belong to lower classes families. The hypothesis of the research is: the knowledge about the federal government programs (ProUni and FIES) depend on the economical and cultural capital of the student, as well as on the social relations established at social and school ambits. The research took place at two schools in the Northwest area of Sao Paulo. The schools were chosen due to their results at the 2007 ENEM examination. We worked with two schools: those that got the best and the lower grades at the 2007 ENEM. We applied the questionary to a 3rd grade evening high school group of each school, coming down to 96 students. We have chosen students from the evening period because there are evidences that identify them as being the economical and social excluded ones lots of them are workers who get tired to school and many times they have learning gaps. With the results we got on the analysis we can state: the students who showed a good knowledge about ProUni are different from those who did not know about it owing to the fact of taking or having taken extracurricular courses, of dedicating hours to study out of the classroom, of using the internet, taking trips, going to museums, theaters and movies. The expectations of those who know ProUni can be abridged as an indispensable means to access the labor market and a way to social ascension. Among all aspects related to social and cultural capital, the subjects from the school with the higher grades at ENEM overcome the ones from the school with the lower grades. The economical capital is practically the same at both schools